Magnetic Resonance Imaging (MRI) Spinal Cord and Canal Measurements in Normal Dogs. (15th March 2013) - Hecht, S.; Huerta, M. M.; Reed, R. B.
Summary The goal of this study was to establish Magnetic resonance imaging (MRI) reference ranges for spinal measurements in normal dogs. Forty dogs (1–10 kg, 11–20 kg, 21–30 kg, > 30 kg; 10 dogs per category) underwent spinal MRI. Measurements were performed on sagittal T2‐W images at the level of the 4th thoracic vertebra (T4), the 9th thoracic vertebra (T9) and the 3rd lumbar vertebra (L3). Spinal canal diameter (mm) ranged from 6.07 ± 0.63 (1–10 kg) to 8.27 ± 1.15 (> 30 kg) at the level of T4; 6.55 ± 0.61 (1–10 kg) to 9.04 ± 1.26 (> 30 kg) at the level of T9; and 6.80 (6.47–7.00; 1–10 kg) to 9.00 (7.90–9.73; > 30 kg) at the level of L3. There were significant differences (P < 0.05) in spinal canal diameter between groups. Mean spinal cord diameter (mm) ranged from 4.46 ± 0.51 (11–20 kg) to 4.70 ± 0.35 (1–10 kg) at the level of T4; 4.41 ± 0.50 (> 30 kg) to 4.85 ± 0.57 (1–10 kg) at the level of T9; and 4.52 ± 0.51 (> 30 kg) to 5.14 ± 0.68 (1–10 kg) at the level of L3. There were no significant differences in spinal cord diameter between groups. Spinal cord‐to‐spinal canal ratio varied significantly, ranging from 0.51 ± 0.08 (> 30 kg at L3) to 0.78 (0.69–0.80; 1–10 kg at T4) (P < 0.05). These findings are important when using MRI to evaluate patients with suspected diffuse spinal cord disease.